Determinants of openness activities in innovation: The mediating effect of absorptive capacity - Héctor Cuevas-Vargas; Neftalí Parga-Montoya; Jeffrey J. Lozano-García; Eduardo Huerta-Mascotte (Journal of Innovation & Knowledge (JIK), 2023)
This research aims at analyzing the effects of entrepreneurial orientation (EO) on absorptive capacity (ACAP) and open innovation (OI) in small Colombian businesses, while also determining whether ACAP significantly influences OI. Additionally, it intends to measure the mediating effect of ACAP on the relationship between EO and OI. The study employed a quantitative approach and cross-sectional design, utilizing structural equation modeling. Data was gathered from a sample of 145 business owners in the department of Bogota, Colombia, using a simple random sampling technique and a self-administered questionnaire. The results indicate that EO strongly influences ACAP. Although no direct significant influence on OI was found, a significant indirect effect was observed. Furthermore, EO has a significant total effect on OI. ACAP was shown to significantly influence OI, demonstrating a full mediating effect on the relationship between EO and OI. These findings have important implications for entrepreneurs and decision-makers and contribute to the development of dynamic capabilities theory.
Keywords: O36; O31; O32; D21; L10; M20; 650; Entrepreneurial orientation; Absorptive capacity; Open innovation; Mediating effect; Indirect effects; PLS-SEM